Artists of the possible governing networks and American policy change since 1945 - Grossmann, Matthew 1979- (Studies in postwar American political development, 2014)
"Policy change is not predictable from election results or public opinion. The amount, issue content, and ideological direction of policy depend on the joint actions of policy entrepreneurs, especially presidents, legislators, and interest groups. This makes policymaking in each issue area and time period distinct and undermines unchanging models of policymaking"--